2020
DOI: 10.1155/2020/5376108
|View full text |Cite
|
Sign up to set email alerts
|

Both Gut Microbiota and Differentially Expressed Proteins Are Relevant to the Development of Obesity

Abstract: Although the role of the gut microbiota in obesity has recently received considerable attention, the exact mechanism is unclear. This study was aimed at investigating the profiles of bacterial communities in fecal samples and differentially expressed proteins (DEPs) in the peripheral blood in mice fed a high-fat diet (HFD) and standard diet (SD) and at providing new insights into the pathogenesis of obesity. The profiles of bacterial communities in fecal samples and DEPs in the peripheral blood were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…Our study proved that the treatment of dapagliflozin attenuated body weight in postinfarction mice significantly (compared with the MI group), which is also consistent. In addition, we found a negative correlation between Desulfovibrionaceae and body weight, which is opposite to the result that the increased Desulfovibrionaceae abundance may lead to glucose/lipid metabolic dysfunction, which is likely to promote body weight gain 41 …”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Our study proved that the treatment of dapagliflozin attenuated body weight in postinfarction mice significantly (compared with the MI group), which is also consistent. In addition, we found a negative correlation between Desulfovibrionaceae and body weight, which is opposite to the result that the increased Desulfovibrionaceae abundance may lead to glucose/lipid metabolic dysfunction, which is likely to promote body weight gain 41 …”
Section: Discussioncontrasting
confidence: 98%
“…In addition, we found a negative correlation between Desulfovibrionaceae and body weight, which is opposite to the result that the increased Desulfovibrionaceae abundance may lead to glucose/lipid metabolic dysfunction, which is likely to promote body weight gain. 41 It was reported that SCFAs are more readily oxidized than ketones during heart failure. 42 However, whether dapagliflozin can attenuate cardiac dysfunction through faecal microbiota by generating SCFAs, or promoting ketogenesis, needs to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…As for horse study, supplementation of Saccharomyces cerevisiae (S. cerevisiae) modulated positively the overall structure of intestinal microbiota with increased relative abundance of Lachnospiraceae (Garber et al, 2020), which is a family of butyrate-producing bacteria (Nicholson et al, 2012;Hamilton et al, 2020). On the other hand, high fat diet resulted in a reduction of the relative abundance of the Bacteroidetes_S24-7_group and Lachnospiraceae in mice, which might be one of the primary etiological mechanisms underlying obesity (Li et al, 2020). Similar to this study, the lower relative abundance of Cetobacterium is accompanied by greater growth performance in tilapia (O. niloticus) (Standen et al, 2015;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…S24-7 is usually considered as an antiobesity gut microbiota, as it improves energy expenditure by producing butyrate. 56 However, some other studies have considered S24-7 to be a bad gut microbiota. 57,58 Matteo Serino et al found more S24-7 in mice fed with a high-fat carbohydrate-free diet, 58 which was in line with our present study.…”
Section: Papermentioning
confidence: 99%